Examining the debate on government's communication strategies for covid-19 management in online media: A content analysis - Panji Dwi Ashrianto; Edwi Arief Sosiawan; Khuswatun Hasanah (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2023)
The Covid-19 pandemic has had far-reaching effects worldwide, impacting various aspects of society and the economy. For this, governments have faced significant challenges in addressing this global crisis. Amidst the outbreak, there have been public debates and disputes surrounding government communication and policies related to Covid-19. The lack of public understanding of the implemented measures has led to criticism of the government's response, seen insufficient and ineffective in communicating with the public. This study focuses on analyzing controversies and debates surrounding government policies during the early stages of the pandemic. Using a quantitative content analysis approach, the study examined policy content sourced from popular Indonesian news media portals. The research findings indicated that the president played a central role in conveying government policies, which primarily focused on macro-level strategies to combat the pandemic. However, the communication of these policies has generated significant controversy and discord among the public.